Pollination systems and floral traits in cerrado woody species of the Upper Taquari region (central Brazil) - Martins,F. Q. (2006)
Plant species present flowers with varied morphological and functional features, which may be associated to pollination systems, including species pollinated by wind, beetles, moths, bees, small insects, birds, or bats. We calculated the frequencies of the pollination systems among woody species in five cerrado fragments in central-western Brazil and tested whether the pollination systems were indeed related to floral traits. We sampled 2,280 individuals, belonging to 121 species, ninety-nine of which were described in relation to all floral traits. Most species had diurnal anthesis, pale colors, and open flowers. The most frequent groups were those composed by the species pollinated by bees, small insects, and moths. A Principal Component Analysis of the species and floral traits showed that there was a grouping among species with some pollination systems, such as those pollinated mainly by beetles, moths, birds, and bats, for which inferences based on the floral traits are recommended in cerrado sites. For the species pollinated mainly by bees or small insects, inferences based on the floral traits are not recommended, due to the large dispersion of the species scores and overlapping between these two groups, which probably occurred due to the specificity absence in plant-pollinator relationships.